Impact of the COVID-19 pandemic on university students’ psychological distress, well-being, and utilization of mental health services in the United States: populations at greatest risk - Russell, Elaine Cooper; Abidogun, Tolulope M.; Lindley, Lisa L.; Griffin, Kenneth W. (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic led to major disruptions in the lives of university students, which is a population that is already at a greater risk of mental health concerns. Little is known about how the pandemic impacted distress and mental health services utilization among university students across the United States. Methods Using survey data from the National College Health Assessment, both before the COVID-19 pandemic (pre-March 2020, n = 88,986) and during the pandemic (Spring 2021, n = 96,489), the present study examined mental health symptoms and utilization of mental health services among undergraduate students attending four-year universities in the United States. Results There were notable increases in measures of psychological distress and reductions in well-being from before the pandemic to during the pandemic. However, overall utilization rates of mental health services slightly decreased from pre-pandemic to during the pandemic. Predictors of severe psychological distress included those who experienced loneliness, COVID-19 related stressors, and loss of a loved one from COVID-19. COVID-related stressors and loneliness were associated with higher utilization rates of mental health services, while well-being and resilience were associated with lower utilization rates. Discussion Analyses revealed that several demographic groups were at an elevated risk for severe psychological distress, including non-binary, female, and sexual minority students, and especially those who identify as both non-binary and non-heterosexual. Results indicated that students of color, especially female students of color, were less likely to receive mental health services. Future research is needed to increase our understanding of the barriers to mental health service use among high-risk university students.